Design and optimization of LDMOS-SCR devices with improved ESD protection performance. (June 2016) - Liang, Hailian; Cao, Huafeng; Gu, Xiaofeng; Guo, Zixiang
Abstract: The lateral diffusion metal-oxide semiconductor embedded silicon controlled rectifier (LDMOS-SCR) devices with optimized structures and layouts for improving the electrostatic discharge (ESD) protection ability have been proposed. The devices are designed and fabricated in 0.25-μm, 0.35-μm and 0.5-μm Bipolar-CMOS-DMOS processes. Firstly, by designing an appropriate stripe resistance in series with the source of the LDMOS-SCR, the holding voltage of the proposed high resistance LDMOS-SCR (HRLDMOS-SCR) increases. Secondly, by inserting a floating Zener-diode into the LDMOS-SCR, the trigger voltage of the modified Zener-diode triggered LDMOS-SCR (ZTLDMOS-SCR) decreases. Finally, the ZTLDMOS-SCR is further optimized by using a ring layout and incorporating a square source resistance, resulting in a significantly improved figure of merit in comparison to traditional LDMOS-SCR devices. The optimized ZTLDMOS-SCR devices are very attractive for constructing effective and latch-up immune high voltage ESD protection solutions in power integrated circuits. Highlights: A series of structures and layouts of LDMOS-SCR devices has been designed and optimized. ESD characteristics of LDMOS-SCR with optimized structure and layouts have been investigated. The Zenertriggered LDMOS-SCR using a ring layout and incorporating the source resistance has the best ESD protection performance.